The Sustainable Leadership for Vocational Schools in Thailand: A Structural Equation Model - Khukrit Silalaiy; Thanin Ratanaolarn; Malai Thaveesuk (My University, 2018)
Abstract The purpose of this research was to study the leaders’ characteristics, situation management, behaviors and roles affecting sustainable leadership development and examine the compatibility of the structural equation model regarding sustainable leadership for vocational education administrators, as developed from the empirical evidence and determined influence of each factor. The quantitative research utilized questionnaires, given to a sample of 404 vocational education principals and vice-principals, derived using a multistage sampling method from 413 vocational public schools in Thailand. To test the confirmatory factor analysis and structural equation model were conducted. This research findings suggest that the structural equation models for sustainable leadership development of vocational education administrators were in accordance with the empirical data. The leaders' characteristics factors had the weight of the maximum gross effects towards the sustainable leadership development. This study suggest that the sustainable leadership development for vocational education administrators can be carried out by developing leaders’ characteristics.
Keywords: Empirical Research; Job Satisfaction and Organizational Behavior